Türkiye’deki Emeklilik Şirketlerinin Etkinlik Analizi - (:unkn) unknown (My University, 2018)
Bu çalışmada 2013 yılının başında yürürlüğe giren Bireysel Emeklilik SistemindeDevlet Katkısı Hakkında Yönetmelik’le getirilen düzenlemelerin emeklilik şirketlerininetkinlikleri üzerindeki yansımaları incelenmiştir. Bu amaçla yasal düzenlemeden önceki üç yılve yasal düzenlemeden sonraki üç yıl Veri Zarflama Analizi kullanılarak incelenmiştir. Genelolarak sektörün kaynaklarını tam etkin kullanamadığı ve 2013 yasal düzenlemesinin sektöretkinliğini olumsuz yönde etkilediği sonucuna ulaşılmıştır.

This study examines whether the regulation (the regulation about the government_x000D_ contribution to pension system-2012) which came into force in the beginning of 2013 affects_x000D_ the efficiency scores of pension companies. To make this analysis, three years before the legal_x000D_ regulation and three years after the legal regulation were considered. It is possible to say that_x000D_ pension sector in Turkey is not efficient and the legal regulations of 2013 made a negative_x000D_ effect on the efficiency scores of pension companies in Turkey.This study examines whether the regulation (the regulation about the government_x000D_ contribution to pension system-2012) which came into force in the beginning of 2013 affects_x000D_ the efficiency scores of pension companies. To make this analysis, three years before the legal_x000D_ regulation and three years after the legal regulation were considered. It is possible to say that_x000D_ pension sector in Turkey is not efficient and the legal regulations of 2013 made a negative_x000D_ effect on the efficiency scores of pension companies in Turkey.
The Efficiency Analysis of Turkish Pension Companies